2017
DOI: 10.1159/000477153
|View full text |Cite
|
Sign up to set email alerts
|

Extrapyramidal Symptoms Probably Related to Risperidone Treatment: A Case Series

Abstract: Background: Atypical antipsychotics, like risperidone purportedly, score over their typical counterparts in terms of their lower propensity toward producing extrapyramidal symptoms (EPS). However, recent studies have furnished evidence to the contrary. Hereby, we present a case series implicating risperidone as the causative agent for EPS. Methods: As a part of the pharmacovigilance programme of India, the authors have assessed 10 physician-reported cases of EPS among the 1,830 patients who were prescribed ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…Similarly, the majority of children in our cohort with extrapyramidal symptoms were on low starting doses of risperidone. Data from multiple fixed-dose (1–16 mg/day and placebo) trials of risperidone in adults with schizophrenia suggested extrapyramidal symptoms are risperidone dose related [ 31 , 32 ]. Those on placebo or low-dose risperidone (1 mg/day) experienced more extrapyramidal symptoms than those on high doses (2–16 mg/day).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the majority of children in our cohort with extrapyramidal symptoms were on low starting doses of risperidone. Data from multiple fixed-dose (1–16 mg/day and placebo) trials of risperidone in adults with schizophrenia suggested extrapyramidal symptoms are risperidone dose related [ 31 , 32 ]. Those on placebo or low-dose risperidone (1 mg/day) experienced more extrapyramidal symptoms than those on high doses (2–16 mg/day).…”
Section: Discussionmentioning
confidence: 99%
“…Os antipsicóticos atípicos, como a risperidona, supostamente têm vantagens importantes sobre os antipisicóticos mais antigos, particularmente em relação à menor incidência de efeitos extrapiramidais (40,61). No entanto, estudo mais recentes forneceram evidências em contrário (62).…”
Section: Efeitos Extrapiramidais (Eep)unclassified
“…A menor propensão ao desenvolvimento de EEP com antipsicóticos atípicos tem sido atribuída à relativamente fraca ligação destes aos receptores D2 em comparação com os antipsicóticos convencionais, como o haloperidol. No entanto, a risperidona é igualmente potente no bloqueio dos receptores D2 e 5-HT2, e sua potência no bloqueio de receptores D2 depende da dose utilizada, possuindo, assim, uma capacidade inata de produzir uma gama de efeitos adversos (62).…”
Section: Efeitos Extrapiramidais (Eep)unclassified
“…1 At risperidone dosages >6 mg/d, the balance between D2 and serotonin-2A (5-HT2A) receptor potency is lost, which increases the potential for EPS. 32 In one RCT, long-acting injectable (LAI) risperidone, up to 100 mg biweekly, was well-tolerated but no more effective for TRS than 50 mg biweekly. 33 A case report suggested improvement of TRS in a patient administered risperidone LAI, 75 mg vs 37.5 mg biweekly, but it is unclear if a 50-mg dosage was tried.…”
Section: Clinical Pointmentioning
confidence: 99%